Design of a Linear Precoder for PAPR Reduction of the OTFS Scheme in High Mobility Environments - Sheikh-Hosseini, Mohsen; Uysal, Murat (IEEE transactions on vehicular technology, 2025)
In this paper, we address the optimal design of a precoder to counteract the degrading effects of high PAPR in OTFS modulation. Using weighted-type fractional Fourier transform (WFRFT) operation as the initial structure of the precoder, we first describe the signal model of the WFRFT-precoded OTFS by employing the precoder either in the delay-Doppler domain or the time domain. Then, we formulate the problem of PAPR reduction as a constrained optimization problem, aiming to design an optimized precoder structure that minimizes the PAPR subject to no adverse effect on the BER. For the solution, we present an algorithm relying on iterative minimization of the moments of the instantaneous power of transmitted data using the gradient descent method. The results confirm that the proposed algorithm leads to a design that outperforms the two benchmark systems and precoding methods, achieving a significant reduction in PAPR without incurring any BER losses. It is also affirmed that the proposed algorithm converges for both delay-Doppler and time domain implementations, and the latter realization has a faster design speed due to its lower computational complexity.